Analisis Strategi Pemasaran Syariah Pada Usaha Batik Dalam Peningkatan Pendapatan Di Kecamatan Pelayangan Kota Jambi - Ahmad Muzni Wildan; Rafidah; Bella Arisha (JOURNAL SAINS STUDENT RESEARCH, 2023)
Sharia marketing strategy is an activity through planning, service, product development and pricing that satisfies consumer needs in accordance with Islamic law. This study aims to analyze the application of sharia marketing strategies in service and product development to increase revenue for batik entrepreneurs in Pelayangan District, Jambi City. This thesis uses leatherative research, the data used are primary data and secondary data. Data is collected through observation and interviews with batik owners in Pelayangan District, Jambi City. The results of this study indicate that some batik entrepreneurs in Pelayangan District, Jambi City have not been optimal in implementing sharia marketing strategies. Sharia marketing strategies can have a positive impact, but it is still necessary to develop an optimal sharia marketing strategy, the development of sharia marketing strategies, especially in product and service promotion in Pelayangan District, Jambi City, of course, there are several obstacles.